Znaki misterium w liryku Zbigniewa Herberta pt. U wrót doliny - Urban, Piotr Dariusz (Przestrzenie Teorii, 2011)
A superior aim of the article was to prove that Zbigniew Herbert’s lyrical works in an unusually clear way gravitate towards drama and theatre. To prove this, the author of the thesis revealed the relationship between the, coming from the volume Hermes, Dog and the Star, lyric At the Gate of the Valley and a mystery play which should be understood not only as a medieval variant of religious drama but also more widely that is in terms of outlook or as an anthropological, historiosophic or metaphoric category. The author of the article showed that for the mystery character of the work speaks not only the subject taken from the Bible or non-Aristotelian action but also sacred character of space-time and, above all, martyrological plot of the lyrical text, showing the suffering of individual characters of the poem as a mirror reflection of the torment of the Saviour. He also noticed that at the beginning of the lyric Herbert used verse which under certain conditions may resemble medieval ways of versification, also typical of dramatic mystery forms and he tried to prove that the author of The Report from a Besieged City, composing his mini drama, used also a film way of watching the stage and the events happening on it. Setting about revealing the relationships between the above-mentioned lyric and a mystery play, the author of the article first showed these signs which indicate the dramatic and theatrical provenance of the poem. He proved that the lyrical subject resigned from the direct characterization of the depicted world and let speak specific stage characters using different forms of dialogue. He showed that the author constructed the statements of individual characters in such a way as to overload them with the surplus of information, typical of stage dialogues. He also proved that the events that the reader follows from the position of the spectator, take place in a specific scenery and the dramatis personae not only have clear psychological construction but they also, as it is proper for the show, use a variety of visual and acoustic signs concerning both the performer and the space. The author of the article deeply hopes that with his thesis he will contribute to enriching traditional analysis of Zbigniew Herbert’s lyrics with such ways of reading that let notice dramatic and theatrical character of his poems.